Comprehensive home-based care coordination for vulnerable elders with dementia: Maximizing Independence at Home-Plus—Study protocol. (December 2017) - Samus, Quincy M; Davis, Karen; Willink, Amber; Black, Betty S; Reuland, Melissa; Leoutsakos, Jeannie; Roth, David L; Wolff, Jennifer; Gitlin, Laura N; Lyketsos, Constantine G; Johnston, Deirdre
Introduction: Despite availability of effective care strategies for dementia, most health care systems are not yet organized or equipped to provide comprehensive family-centered dementia care management. Maximizing Independence at Home-Plus is a promising new model of dementia care coordination being tested in the U.S. through a Health Care Innovation Award funded by the Centers for Medicare and Medicaid Services that may serve as a model to address these delivery gaps, improve outcomes, and lower costs. This report provides an overview of the Health Care Innovation Award aims, study design, and methodology. Methods: This is a prospective, quasi-experimental intervention study of 342 community-living Medicare–Medicaid dual eligibles and Medicare-only beneficiaries with dementia in Maryland. Primary analyses will assess the impact of Maximizing Independence at Home-Plus on risk of nursing home long-term care placement, hospitalization, and health care expenditures (Medicare, Medicaid) at 12, 18 (primary end point), and 24 months, compared to a propensity-matched comparison group. Discussion: The goals of the Maximizing Independence at Home-Plus model are to improve care coordination, ability to remain at home, and life quality for participants and caregivers, while reducing total costs of care for this vulnerable population. This Health Care Innovation Award project will provide timely information on the impact of Maximizing Independence at Home-Plus care coordination model on a variety of outcomes including effects on Medicaid and Medicare expenditures and service utilization. Participant characteristic data, cost savings, and program delivery costs will be analyzed to develop a risk-adjusted payment model to encourage sustainability and facilitate spread.